Green Intellectual Capital, Surplus Free Cash Flow, and Audit Quality: The Moderating Role of Busy Commissioners - Tandry Whittleliang Hakki; Winola Alvina Finanda; Shello Ceolitta Pranoto; Yosua Samuel Ramli (The Es Accounting And Finance, 2026)
This study examines the effect of Green Intellectual Capital (GIC) and Surplus Free Cash Flow (SFCF) on audit quality, as well as the moderating role of busy commissioners. Using a quantitative explanatory design, this study analyzes 156 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange during 2019–2024. Audit quality is measured using a KAZNIC-based composite score, while GIC is measured through content analysis of annual and sustainability reports. The data are analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show mixed evidence. GIC has a positive but insignificant effect on audit quality, indicating that green knowledge resources do not automatically improve audit outcomes. SFCF has a positive and significant effect, suggesting that firms with higher surplus cash require stronger external monitoring. Busy commissioners show a positive direct association with audit quality. However, the moderating effects are not uniformly supportive. Busy commissioners do not significantly strengthen the GIC–audit quality relationship, while they negatively moderate the SFCF–audit quality relationship. These findings suggest that commissioner busyness may provide governance benefits, but excessive commitments may weaken monitoring effectiveness in agency-sensitive financial conditions.